2023
DOI: 10.1021/acs.langmuir.3c00335
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Janus Liposome Micromotors

Abstract: A liposome-based micromotor system that utilizes regional enzymatic conversion and gas generation to achieve directional motion in water is presented. Constituted mainly of a low-melting lipid and a high-melting lipid together with cholesterol, these liposomes maintain stable Janus configuration at room temperature as a result of lipid liquid−liquid phase separation. Local placement of enzymes such as horseradish peroxidase is realized via affinity binding between avidin and biotin, the latter as a lipid conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
4
0
4
Order By: Relevance
“…In 2019, Ghosh et al showed that GUVs with ATPase-tagged lipid membranes exhibited enhanced mobility in the presence of ATP. 286 In 2023, Jin et al demonstrated that horseradish peroxidase (HRP)-decorated Janus GUVs undergo directional motion in the presence of H 2 O 2 , while such enhanced mobility is absent from homogeneously enzyme-decorated GUVs 287 ( Fig. 11(c) ).…”
Section: Actuators Of Molecular Robotsmentioning
confidence: 99%
“…In 2019, Ghosh et al showed that GUVs with ATPase-tagged lipid membranes exhibited enhanced mobility in the presence of ATP. 286 In 2023, Jin et al demonstrated that horseradish peroxidase (HRP)-decorated Janus GUVs undergo directional motion in the presence of H 2 O 2 , while such enhanced mobility is absent from homogeneously enzyme-decorated GUVs 287 ( Fig. 11(c) ).…”
Section: Actuators Of Molecular Robotsmentioning
confidence: 99%
“…[8] Additionally, Janus architectures with asymmetric magnetic properties can give rise to notable performances in drug delivery, [9,10] biological imaging and probes, [11,12] and directional motion. [13,14] Aside from the traditional spherical Janus particles, 1D Janus rods and 2D Janus nanosheets are also feasible, albeit typically more challenging to prepare. [15][16][17] Notably, 2D Janus nanosheets have been the subject of significant interest due to their high aspect ratio, highly anisotropic shape and chemistry, as well as the highly confined rotation at interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…We used different populations of enzyme-functionalized liposomes and/or solid particles that are part of catalytic reaction cascades. The addition of the substrate for the first population results in the enhanced motility of those particles. , At the same time, the chemical product formed serves as the substrate for the second population and enhances their motility. The process continues in populations involving three enzymes, resulting in enhanced motility of the third population.…”
Section: Introductionmentioning
confidence: 99%